Tackling Bias Against Women Victims of Sexual Assault in the Chilean Judiciary: A Case Study - Parodi Ambel, Karime (2023)
Women victims of sexual assault encounter several hurdles when seeking justice in Chilean legal institutions; however, recent efforts by the Chilean Supreme Court to fight bias against underrepresented groups have foregrounded the importance of applying a gender perspective in court trials. In light of the publication by the Chilean Supreme Court in 2019, I analyze the court ruling of a 2004 rape case that led Corporación Humanas?a feminist NGO?to file a petition before the Inter-American Commission on Human Rights. Given the ruling’s egregious biases, the NGO holds Chile responsible for the violation of several victims’ rights specified in international human rights treaties. Based on the written court ruling, I examine how the judges and other legal actors failed to deliver justice with a gender perspective. For that purpose, I analyze how the judges, the prosecutors, and the defense attorneys resorted to the following types of gender bias: a) gender stereotypes and rape myths, b) credibility discounting (Tuerkheimer, 2017), c) assessment of the evidence without a gender perspective, d) requirement of bodily injury to give credence to the hypothesis of rape by force and e) discussion of the victim’s sexual history. Considering the different categories of gender bias detected in the case, I assess whether the Chilean handbook would have been an effective tool to prevent them. Finally, based on this case, I determine the handbook’s limitations and suggest potential improvements.